2007
DOI: 10.1128/jb.00190-07
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component Regulatory System senX3-regX3 Regulates Phosphate-Dependent Gene Expression in Mycobacterium smegmatis

Abstract: Phosphate import is required for the growth of mycobacteria and is regulated by environmental inorganic phosphate (P i ) concentrations, although the mechanism of this regulation has not been characterized. The expression of genes involved in P i acquisition is frequently regulated by two-component regulatory systems (2CRs) consisting of a sensor histidine kinase and a DNA-binding response regulator. In this work, we have identified the senX3-regX3 2CR as a P i -dependent regulator of genes involved in phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(173 citation statements)
references
References 43 publications
6
141
0
1
Order By: Relevance
“…Accumulating evidence has suggested that SenX3-RegX3 is directly involved in the mycobacterial phosphate starvation response (Glover et al, 2007;James et al, 2012;Rifat et al, 2009). P i limitation is believed to be a physiologically relevant microenvironment encountered by Mtb within the arrested macrophage phagolysosome (Rengarajan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accumulating evidence has suggested that SenX3-RegX3 is directly involved in the mycobacterial phosphate starvation response (Glover et al, 2007;James et al, 2012;Rifat et al, 2009). P i limitation is believed to be a physiologically relevant microenvironment encountered by Mtb within the arrested macrophage phagolysosome (Rengarajan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To study the promoter activities of senX3 and the IR, the Escherichia coli-mycobacterium shuttle vector pYUB76 harbouring the lacZ gene (kind gift of Dr William R. Jacobs, Jr, Albert Einstein College of Medicine, NY, USA) was used (Barletta et al, 1992;Glover et al, 2007). Briefly, a 199 bp segment of the 59 UTR of senX3 was PCR-amplified using primers dl9-F and dl10-R (Table 1) from Mtb CDC1551 genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations